2019
DOI: 10.14710/jitaa.44.4.400-407
|View full text |Cite
|
Sign up to set email alerts
|

Calliandra calothyrsus and Artocarpus heterophyllus as anti-parasite for Bligon Goat

Abstract: This study investigated the nutritional potency and efficacy of tannin-containing forages as anti-parasites sources to support the performance of female Bligon goats. Fifteen female Bligon goats were divided into 3 different groups based on feeding treatments. The first group (KG) served as the control and was fed 100% king grass (dry matter basis). The second group (KGC) was fed 50% king grass and 50% Calliandra calothyrsus leaves (dry matter basis). The third group (KGA) was fed 50% king grass and 50% Artoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Tuy nhiên, DM của cọng mít ở P2 và P3 là tương đương (lần lượt là 32,1 và 31,9%) và cao hơn (P<0,05) DM của cọng mít ở P1 (29,6%), kết quả này tương đương với nghiên cứu của Van et al (2005). Phần trăm OM của lá mít ở các nghiệm thức khác biệt có ý nghĩa (P<0,05), OM của lá mít ở P2 cho kết qủa cao nhất (86,9%) và thấp nhất là P3 (86,1%), kết quả này phù hợp với nghiên cứu của Setyono et al (2018) là 86,2%. Hàm lượng OM của cọng mít không có sự khác biệt giữa các nghiệm thức và dao động trong khoảng 88,4-88,7%.…”
Section: Thành Phần Hóa Học Của Lá Và Cọng Mítunclassified
“…Tuy nhiên, DM của cọng mít ở P2 và P3 là tương đương (lần lượt là 32,1 và 31,9%) và cao hơn (P<0,05) DM của cọng mít ở P1 (29,6%), kết quả này tương đương với nghiên cứu của Van et al (2005). Phần trăm OM của lá mít ở các nghiệm thức khác biệt có ý nghĩa (P<0,05), OM của lá mít ở P2 cho kết qủa cao nhất (86,9%) và thấp nhất là P3 (86,1%), kết quả này phù hợp với nghiên cứu của Setyono et al (2018) là 86,2%. Hàm lượng OM của cọng mít không có sự khác biệt giữa các nghiệm thức và dao động trong khoảng 88,4-88,7%.…”
Section: Thành Phần Hóa Học Của Lá Và Cọng Mítunclassified
“…Research [10]showed that total condensed tannin in Calliandra decreased by increasing temperature during the process in aerobic condition. Giving 320 gram DM calliandra /day for bligon goat can increase feed intake and improve daily body weight gian [11]. This Study aims to determine the effect of calliandra powder supplemention on the qualtity of sapera goat's milk.…”
Section: Introductionmentioning
confidence: 99%
“…Some important parts of the integrated helminth control program are improving livestock nutrition, proper grazing management, and genetic selection [6]. Furthermore, the provision of various Indonesian local forages for ruminants has been shown to have anthelmintic properties due to ingredients that can harm parasitic worms [7][8][9][10].…”
mentioning
confidence: 99%